2022
DOI: 10.3390/jfmk7010014
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Flywheel Inertia Training to Enhance Hamstring Strength

Abstract: The purpose of this narrative review is to examine the efficacy of flywheel inertia training to increase hamstring strength. Hamstring strain injury is common in many sports, and baseline strength deficits have been associated with a higher risk of hamstring strain injury. As a result, strength and conditioning professionals actively seek additional techniques to improve hamstring strength with the aim of minimising the incidence of hamstring strain injury. One method of strength training gaining popularity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
1
11
0
1
Order By: Relevance
“…a minimum of 3 sessions) and technical proficiency are the key prerequisites for effective FIT adaptations and outcomes [67,92,174,191]. Indeed, those with more FIT experience exhibit a significantly greater eccentric and concentric peak force output [192]; therefore, a detailed report of participants training status and experience is essential in future FIT research.…”
Section: Sprint and Cod Performancementioning
confidence: 99%
“…a minimum of 3 sessions) and technical proficiency are the key prerequisites for effective FIT adaptations and outcomes [67,92,174,191]. Indeed, those with more FIT experience exhibit a significantly greater eccentric and concentric peak force output [192]; therefore, a detailed report of participants training status and experience is essential in future FIT research.…”
Section: Sprint and Cod Performancementioning
confidence: 99%
“…Flywheel eccentric training has been shown to promote positive adaptations to protect athletes from muscle and joint injuries (68) and being an effective training method for the treatment of tendinopathies (16). Studies performed in team sport athletes have shown flywheel eccentric training to be effective in reducing the number of injuries in a season (5,24), which could be related to the specific neuromuscular adaptations such as increased muscle fascicle length (5,79) and 3 only specify strength, injury prevention, and power objectives, exercises and movements that are specific to COD enhancement or speed can be also added. In this sense, as part of the strength protocol, we would include COD-focused exercises using flywheel eccentric training, whereas during the power session, speed exercises would be recommended.…”
Section: Injury Preventionmentioning
confidence: 99%
“…Flywheel eccentric training has been shown to promote positive adaptations to protect athletes from muscle and joint injuries (68) and being an effective training method for the treatment of tendinopathies (16). Studies performed in team sport athletes have shown flywheel eccentric training to be effective in reducing the number of injuries in a season (5,24), which could be related to the specific neuromuscular adaptations such as increased muscle fascicle length (5,79). In any respect, these studies compared flywheel eccentric training with a control group.…”
Section: Training Effects After Flywheel Eccentric Trainingmentioning
confidence: 99%
“…The Romanian deadlift (RDL) exercise is a large multi-joint movement often incorporated to enhance hip extension and flexion [ 13 ]. O’Brien et al [ 14 ] reported the biomechanical disadvantages of the RDL during the FIT exercise, concluding that the postural angle of the “supine open chain” during the loading phase influences the inertial power relationship. Moreover, posterior chain injuries are among the most commonly reported within sports medicine for elite athletes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%